Cell-mediated immunity to gluten fraction III in adult coeliac disease. Issue 2 (February 1978) - Bullen, A W; Losowsky, M S
Abstract : A migration inhibition test was used to assess sensitisation of blood leucocytes, and thus cell-mediated immunity, to gluten fraction III in controls and patients with coeliac disease. Migration indices were significantly less (indicating sensitisation) in untreated and in treated patients than in controls, and significantly less in treated patients than in untreated patients. At a concentration of 1 mg/ml gluten fraction III, 13% of untreated patients and 54% of treated patients had migration indices in the sensitised range. At 2 mg/ml gluten fraction III, sensitisation was demonstrated in 8% of untreated patients and 48% of treated patients. After starting a gluten free diet, migration indices fell into the sensitised range in all patients followed. After at least nine months on a gluten free diet, migration indices were significantly higher in those patients with a normal interepithelial lymphocyte count than in those patients with a raised interepithelial lymphocyte count. Cell-mediated immunity to gluten fraction III can be detected in the peripheral blood of certain patients with coeliac disease. Detectable sensitivity is related to the time on a gluten free diet, and the interepithelial lymphocyte count.